Buckle up safely: a cluster randomised trial to evaluate the effectiveness of a pre-school based program to increase appropriate use of child restraints - Hunter Kate; Bilston Lynne E; Brown Julie; Keay Lisa; Ivers Rebecca Q; Simpson Judy M; Stevenson Mark (BMC, 2011)
Abstract Background Road traffic crashes for car occupants are a leading cause of death and serious injury in children from high and middle income countries globally. Correct use of appropriate child restraints can significantly reduce death and serious injury but there is a need for well powered trials to examine effectiveness of programs to increase optimal child restraint practices. The aim of this trial is to examine the effectiveness of a comprehensive intervention to increase the use of appropriate child restraints, and decrease incorrect use of child restraints in pre-school aged children traveling in cars. Methods and Design A cluster randomised controlled trial will be conducted, involving 28 pre-school or childcare centres in low income areas of Sydney, Australia, over one calendar year. The intervention is an educational program involving an in-service for centre staff, distribution of educational materials to parents, a parent workshop demonstrating restraint use, subsidised restraints for parents in need, and vouchers for a free restraint checking service. Blinded assessors will observe restraint use at all centres at the end of the calendar year. Data will be analysed on an intention-to-treat basis; the primary analysis will compare the proportion of each of the two outcome measures (use of appropriate restraints, and incorrect use of restraints) at each centre between intervention and control groups. Detailed process evaluation will be conducted, including examination of implementation and utilisation of various elements of the program by both centres and families. Discussion This assessor blinded cluster randomised trial is powered to provide credible evidence about the efficacy of an education and distribution program in a pre-school setting to increase appropriate use, and decrease incorrect use of child restraints. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12609000612213.